Application of the Sinusoidal Voltage for Detection of the Resonance in Inductive Voltage Transformers - Michal Kaczmarek (MDPI AG, 2021)
In the case of the inductive voltage transformer (VT), the resonance phenomenon may be the main reason for its poor transformation accuracy of the non-sinusoidal voltage. This problem mainly results from the leakage inductance and the parasitic capacitance of its primary winding. The application of the sinusoidal voltage with a frequency from 20 Hz to 20 kHz presented in this study ensures proper identification of the resonance frequencies of the medium-voltage (MV) inductive VTs. The results are consistent with the values obtained in the reference condition at their nominal primary voltage. Therefore, it is proven that the proposed solution is effective in all cases. The influence of the main frequency variation of the non-sinusoidal primary voltage on the resonance properties of the inductive VT is also studied. Moreover, the tests indicate that the capacitance of the load of the secondary winding may cause a decrease in their resonance frequency.